2009
DOI: 10.1038/onc.2009.30
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PIP3-dependent Rac exchanger 1 (P-Rex1) promotes prostate cancer metastasis

Abstract: Excessive activation of G-protein coupled receptor (GPCR) and receptor tyrosine kinase (RTK) pathways has been linked to prostate cancer metastasis. Rac activation by guanine-nucleotide exchange factors (GEFs) plays an important role in directional cell migration, a critical step of tumor metastasis cascades. We found that upregulation of P-Rex1, a Rac-selective GEF synergistically activated by Gβγ freed during GPCR signaling and PIP3 generated during either RTK or GPCR signaling, strongly correlates with meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
152
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(168 citation statements)
references
References 42 publications
14
152
2
Order By: Relevance
“…Additionally, PREX1 appears to have a specific role in metastasis. The expression of PREX1, but not a GEF-dead mutant, induces spontaneous metastasis in a xenograft prostate cancer mouse model (24), and PREX1 inactivation in mice reduces metastasis in a melanoma transgenic mouse model (23). PREX2 is also overexpressed in numerous cancer types and is frequently mutated in cancer, with especially high mutation rates in melanoma (25)(26)(27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PREX1 appears to have a specific role in metastasis. The expression of PREX1, but not a GEF-dead mutant, induces spontaneous metastasis in a xenograft prostate cancer mouse model (24), and PREX1 inactivation in mice reduces metastasis in a melanoma transgenic mouse model (23). PREX2 is also overexpressed in numerous cancer types and is frequently mutated in cancer, with especially high mutation rates in melanoma (25)(26)(27).…”
mentioning
confidence: 99%
“…PREX1 is overexpressed in a variety of human cancers, including melanoma and breast, prostate, and colon cancer (17,(23)(24)(25)(26). PREX1 knockdown decreases tumor growth in xenograft mouse models of cancer using breast cancer cell lines (17,18).…”
mentioning
confidence: 99%
“…P-Rex2a levels are increased in some human cancers bearing wild-type phosphatase and tensin homolog and mutated PIK3CA, and provokes activation of the phosphoinositide 3-kinase route (Fine et al, 2009). In addition, increased expression of P-Rex1 in prostate cancer has been described, and its presence has been linked to Rac-mediated metastatic potential of prostate cancer cells (Qin et al, 2009). …”
mentioning
confidence: 99%
“…More recently, small molecule inhibitors of Gβγ subunit signaling have been identified that bind to the Gβγ hot spot and inhibit Gβγ protein-protein interactions (16). These have been used in cellular and animal models to further implicate Gβγ signaling as a potential therapeutic target in pain (17), inflammation (18), and cancer (19). Understanding the flexible nature of this surface is important for developing approaches to target Gβγ with "drug-like" molecules for treatment of disease.…”
mentioning
confidence: 99%